Fertilizer use efficiency and economic viability in maize production in the Savannah and transitional zones of Ghana - Adzawla, William; Setsoafia, Edinam D.; Setsoafia, Eugene D.; Amoabeng-Nimako, Solomon; Atakora, Williams K.; Camara, Oumou; Jemo, Martin; Bindraban, Prem S. (Frontiers in Sustainable Food Systems, 2024)
Increasing fertilizer use is highly justified for sustainable agricultural intensification if yield response, fertilizer use efficiency (FUE), and economic viability of fertilizer application are high. Despite the increasing fertilizer application rates in Ghana, yields only marginally increased. Also, the recent fertilizer price hikes post COVID-19 revived concern for economic analysis of fertilizers. This study analyzed the FUE and economic viability of fertilizer use in maize production in Guinea/Sudan Savannah and Transitional/Deciduous zones of Ghana. Survey data from 2,673 farmers in the 2019, 2020, and 2021 production seasons were used. The average agronomic efficiency (AE), partial factor productivity (PFP), and value-cost ratio (VCR) of fertilizer use were 2.2 kg of grains per kilogram of fertilizer, 18.3 kg grains per kilogram of fertilizer, and 1.8 Ghana cedis of marginal yield per Ghana cedi spent on fertilizer, respectively. Fertilizer use was economically viable for only 28.1% of farmers with a VCR of 2 or higher, while 52.5% reached the break-even point with a VCR of at least 1. Various fertilizer formulations, including NPK plus sulfur, and adoption of integrated soil fertility management (ISFM) practices, particularly improved seeds, organic fertilizers, and minimum tillage, improved maize yield response to fertilizer and thus the FUE. These low efficiency and economic viability of fertilizer use are prevailing conditions in other sub-Saharan Africa (SSA) countries and these do not guarantee sustainable food security and improved livelihood of the farmers in the region. Ghana’s Ministry of Food and Agriculture (MoFA), together with relevant stakeholders, should provide guidance on ISFM and intensify farmer education through farmer associations to increase the adoption of ISFM. The local government should work with other relevant stakeholders to improve the market conditions within the agriculture sector, for instance, by linking farmers to city markets for favorable output prices.